Home‐based high‐intensity interval training reduces barriers to exercise in people with type 1 diabetes. Issue 4 (25th October 2019) - Scott, Sam N.; Shepherd, Sam O.; Strauss, Juliette A.; Wagenmakers, Anton J. M.; Cocks, Matt
Abstract : New Findings: What is the topic of this review? This symposium review provides an overview of the recent work investigating whether a virtually monitored home‐based high‐intensity interval training (Home‐HIT) intervention reduces the fear of hypoglycaemia and other common barriers to exercise in people with type 1 diabetes. What advances does it highlight? Home‐HIT seems to offer a strategy to reduce fear of hypoglycaemia, while simultaneously removing other known barriers that prevent people with type 1 diabetes from taking up exercise, because it is time efficient, requires no travel time or costs associated with gym memberships, and allows people to exercise in their chosen environment. Abstract: People with type 1 diabetes (T1D) are recommended to engage in regular exercise for a variety of health and fitness reasons. However, many lead a sedentary lifestyle and fail to meet the physical activity guidelines, in part because of the challenge of managing blood glucose concentration and fear of hypoglycaemia. A number of strategies designed to help people with T1D to manage their blood glucose during and after exercise have been investigated. Although many of these strategies show promise in facilitating blood glucose management during and after exercise, they do not target the many other common barriers to exercise that people with T1D face, such as difficulty with cost and travel time to gyms, limited access to exercise bikes and treadmills, and a possible dislike of exercising in front of others in public places. In this symposium review, we provide an overview of ongoing research into a virtually monitored home‐based high‐intensity interval training (Home‐HIT) programme that is designed to reduce these other common barriers to exercise. The conclusion of this review is that Home‐HIT seems to offer a strategy to reduce fear of hypoglycaemia, while simultaneously removing other known barriers preventing people with T1D from taking up exercise, such as being time efficient, requiring no travel time or costs associated with gym memberships, and giving them the opportunity to exercise in their chosen environment, reducing the embarrassment experienced by some when exercising in public. Abstract :